2004
DOI: 10.3168/jds.s0022-0302(04)73536-5
|View full text |Cite
|
Sign up to set email alerts
|

Noncoagulation of Milk in Finnish Ayrshire and Holstein-Friesian Cows and Effect of Herds on Milk Coagulation Ability

Abstract: The objectives of this study were to compare milk coagulation ability (MCA) and the prevalence of noncoagulation of milk within the main Finnish dairy breeds, Finnish Ayrshire (FA) and Holstein-Friesian (HOL), as well as to study the herd effect on MCA. Data used in the statistical analyses consisted of individual milk samples of 959 FA, 399 HOL, and 50 crossbred cows from 84 herds. Data were collected before the grazing season in the spring 1999. Milk samples were analyzed for the milk coagulation traits (mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
78
5
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(114 citation statements)
references
References 19 publications
29
78
5
2
Order By: Relevance
“…Regarding the effect of parity on milk clotting ability, the literature reports controversial results. Similar to our study, Tyrisevä et al (2003) and Penasa et al (2014) reported that MCP deteriorated with parity, whereas Ikonen et al (2004) and Tyrisevä et al (2004) found better performance in later-than first-parity cows.…”
Section: Effects Of Breed Days In Milk and Parity On Milk Coagulatiosupporting
confidence: 90%
“…Regarding the effect of parity on milk clotting ability, the literature reports controversial results. Similar to our study, Tyrisevä et al (2003) and Penasa et al (2014) reported that MCP deteriorated with parity, whereas Ikonen et al (2004) and Tyrisevä et al (2004) found better performance in later-than first-parity cows.…”
Section: Effects Of Breed Days In Milk and Parity On Milk Coagulatiosupporting
confidence: 90%
“…Average values for MCP and milk composition are worse than those of Cecchinato et al (2009) in Italian Brown Swiss, who reported means of 15.0 min for RCT and 41.7 mm for a 30 evaluated using the computerized renneting meter, and by Bonfatti et al (2011) in Italian Simmental, who reported RCT and a 30 of 16.51 min and 29.08 mm, respectively, using the same mechanical device. Ikonen et al (2004) found 11.80 6 5.50 min for RCT and 24.0 6 13.3 mm for a 30 in Finnish Ayrshire and Tyrisevä et al (2004) reported 11.2 6 5.0 min for RCT and 26.5 6 11.8 mm for a 30 in Finnish Ayrshire, Holstein and crossbred cows. Vallas et al (2010) analyzed log-transformed RCT in Estonian Holstein population and found an average value of 2.3 (CV of 9%) and an average a 30 of 27.0 mm (CV of 27%).…”
Section: Discussionmentioning
confidence: 94%
“…Besides the aforementioned factors, additive genetic effects seem to influence the occurrence of NC milk (e.g. Ikonen et al, 2004;Tyrisevä et al, 2004). The inclusion of NC information in statistical models aiming at estimating covariance components for MCP may influence the assessment of genetic parameters for coagulation traits (Ikonen et al, 2004), but the impact depends mainly on the proportion of NC samples: the lower the proportion, the lower the influence on covariance components.…”
Section: Discussionmentioning
confidence: 99%
“…About 10% of Fay cows produce noncoagulating milk (Ikonen et al 1999a(Ikonen et al , 2004Tyrisevä et al 2004), and some cows produce it persistently (Tyrisevä et al 2003). This milk does not coagulate at all in a standard 30-min testing time.…”
mentioning
confidence: 99%
“…Because a major part of the milk currently produced is used for cheese production (Eurostat 2007), selection of breeding animals for milk coagulation ability is a tempting choice to produce high-quality milk for cheese dairies. The best selection option is still under research (Ikonen 2000;Tyrisevä et al 2003Tyrisevä et al , 2004Ikonen et al 2004;Ojala et al 2005) since due to a lack of high throughput, automated measuring device possibilities for direct selection are limited.…”
mentioning
confidence: 99%